A serially cascaded micro-ring resonator for simultaneous detection of multiple analytes. (12th March 2019) - Butt, M A; Khonina, S N; Kazanskiy, N L
Abstract: We report a serially cascaded micro-ring resonator based on a hybrid plasmonic waveguide for simultaneous detection of multiple analytes. Two micro-ring resonators are deployed with different ring radiuses, with different resonance wavelengths serially coupled to a silicon strip waveguide. The free spectral range (FSR) is obtained at 160 nm by choosing the appropriate ring radius. A large FSR provides the freedom of detection without the resonance shifts of two rings coinciding. The sensitivity of the device depends exclusively on the ring radius and can be adjusted based on the requirements. The best sensitivity of 192 nm/RIU and 232 nm/RIU is obtained for the ring radiuses of 1.8 µ m and 2.0 µ m, respectively.